Validity of Surrendering Cessies Without Debtor Notification in Sharia Banking Bankruptcy Cases - Farhansyah, Adam; Agustina, Rani Sri; Efriyanto, Efriyanto (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2024)
Bankruptcy refers to circumstances where a debtor or company can not fulfill its obligation reimbursement commitments to creditors through the Liquidation Regulation and PKPU guidelines. Cessie, specifically the appointment of claim rights from the initial claimant (cedent) to the new biller (cessionary). When there is a transfer of debt collection rights (cessie) without giving notification to the debtor who is the party requested for bankruptcy during the PKPU procedure because it is still in a civil and criminal dispute, it becomes the focus of this research. Focal Jakarta Commercial Court Choice Number: 25/Pdt.Sus-Pailit/2020/PN.Niaga.Jkt.Pst. got to be the question of this inquiry about, with the purpose in breaking down the authenticity of the cessie which was carried out without giving notice to the indebted person as the party respondent in insolvency within the insolvency case. Normative legal research is an exploratory method applied in this research. The agreement in the cessie deed between the cedent and the cessie does not bind the cessus even without notice so that if the parties do not notify the cessus, the cessie confirmed in the authentic deed only has legal force binding on the parties which is considered the same as a deed under the hand, so that even without notification to the cessus, the cessie remains valid.